Academic entrepreneurship in a resource contrained environment: Diversification and synergistic effects - L. Ranmuthumalie de Silva; Elvira Uyrarra; Ray Oakey (The University of Manchester, Manchester Business School, 2011)
This paper investigates the nature of academic entrepreneurial engagement in a resource constrained environment. In addition to context-specific contributions, the paper adds originality to the academic entrepreneurship literature by discussing diversification strategies adopted by academic entrepreneurs, and synergies among academic entrepreneurial activities. Mixed methods are used in a sequential manner; 1. Initial context specific data gathering stage 2. On-line survey 3. In-depth face to face interview phase. The survey response rate is 30% (358 academics), and the sample size of in-depth interviews is 78. Findings reveal that resource barriers do not suppress academic engagement in entrepreneurial endeavour. Instead, academics consider being entrepreneurial as a means to be resource-rich. It is also revealed that academics gradually diversify their engagements, and due to limited opportunities, they tend to engage in unrelated diversification. In resource constrained environments unrelated diversification is found to generate more synergistic effects than related diversification. Policy implications and future research avenues are highlighted.
Keywords: 330; Academic entrepreneurship; Resource constraints; Developing country; Social network; Diversification; Synergistic effects; Unternehmensgründung; Akademiker; Diversifikation; Soziales Netzwerk; Synergie; Ressourcenorientierter Ansatz; Sri Lanka